Effective Phosphate Removal from Synthesized Wastewater Using Copper-Chitosan Bead: Batch and Fixed-Bed Column Studies - An, Byungryul; Jung, Ka-Young; Lee, Sang-Hyup; Lee, Seunghak; Choi, Jae-Woo (Kluwer Academic Publishers, 2014)
To remove phosphate from solution, a new class of sorbent based on chitosan bead (CB) was prepared using copper ion (Cu(II)) with/without a traditional crosslinking agent (glutaraldehyde [GLA]); these materials are referred to as CB-G-Cu and CB-Cu, respectively. Copper ions play a key role in the CB synthesis; these species crosslink each polymer chain, and during phosphate removal, they are the active functional group. Overall, 2.5 % (w/w) of chitosan is necessary to maintain the physical properties of the bead. In the FTIR spectra, adding GLA decreased the intensity of the amino group in chitosan, lowering the amount of copper in the CB. The maximum phosphate uptake (Q) for CB-Cu was 53.6 mg g(-1) when calculated with the Langmuir isotherm, and the phosphate equilibrium was achieved in 12 h. Although the solution pH was not strongly affected, values below 7 are optimal for phosphate removal. The CB-Cu can be feasibly applied during a fixed column test, revealing that the phosphate breakthrough was 1.5 times higher than with CB-G-Cu.